Pengaruh Metode Pembelajaran Menggunakan Mind Mapping terhadap Kemampuan Berpikir Kreatif Siswa pada Mata Pelajaran Akidah Akhlak Kelas XII di MAN 3 AGAM - Shofiyah Salsabila Harahap; Zulfani Sesmiarni (YASIN, 2026)
Although the development of creative thinking skills has received attention in various educational studies, research specifically examining the effect of the Mind Mapping method on creative thinking skills in Akidah Akhlak learning at the Madrasah Aliyah level remains limited. This study aimed to analyze the effect of the Mind Mapping method on the creative thinking skills of Grade XII students in the Akidah Akhlak subject at MAN 3 Agam. The study employed a quantitative approach with a quasi-experimental design in the form of a non-equivalent control group design, involving 60 students selected through purposive sampling and divided into experimental and control groups. Data were collected using an essay test based on four creativity indicators, namely fluency, flexibility, originality, and elaboration, which had been tested for validity and reliability, and were then analyzed using normality and homogeneity tests, gain score calculation, and an independent-samples t-test with the assistance of SPSS. The results showed a significant difference between the experimental and control groups (p < 0.05), with a greater improvement in creative thinking skills among the group that used the Mind Mapping method. These findings reinforce constructivist theory and divergent creativity theory in the context of Pendidikan Agama Islam learning and extend understanding of innovative instructional strategies in madrasahs. The study concludes that the use of visual- and association-based learning methods is important for improving students’ higher-order thinking skills and recommends that Akidah Akhlak teachers integrate Mind Mapping into the learning process. The implications of this study include a theoretical contribution to enriching the literature on creative learning in Islamic education and practical implications for educational institutions in designing more participatory learning strategies oriented toward 21st-century skills.